Mini Review/Commentary: Growth Hormone Treatment in Children with Type 1 Diabetes - Bonfig, Walter; Holl, Reinhard W. (International journal of molecular sciences, 2019)
In the state of insulin deficiency, the growth hormone—insulin-like growth factor-I (GH–IGF-I) axis is altered due to hepatic GH resistance, which leads to GH hypersecretion and low circulating IGF-I concentration. On the other hand, both growth hormone deficiency (GHD) and GH excess have significant influence on carbohydrate metabolism. These complex interactions are challenging in diagnosing GHD in subjects with type 1 diabetes mellitus (T1DM) and in treating subjects with T1DM with GH. So far, there is only limited clinical experience in GH treatment in patients with T1DM, but recently first reports on metabolic safety and efficacy of GH treatment in subjects with T1DM have been published.